PENATALAKSANAAN TEKNIK LOTUS BIRTH PADA PERSALINAN DI KLINIK SHANTY MEDAN - Elvalini Warnelis Sinaga; Sundari Putri Wijaya (Jurnal Ilmiah Kebidanan Imelda, 2023)
Ante-Natal Care (ANC) is a health service by professionals provided to mothers during pregnancy which is carried out in accordance with antenatal care standards. The delay in cutting the umbilical cord is to leave the umbilical cord uncut for at least 1 hour which is believed to increase immunity in newborns. This study aims to conduct advanced midwifery care with a delay in cutting the umbilical cord at the Shanty Clinic. The research method is a case study. Management is carried out with a continuous of care approach, namely midwifery care for Ny. A G1P0A0 starting from Pregnancy, Childbirth, BBL, Postpartum and Family Planning at the Shanty Maternity Clinic. Comprehensive midwifery care for Mrs. "A" received complaints that were felt to be still in physiological terms and management had been carried out according to the complaints and in accordance with the physiological results and management in accordance with the conditions in patients during pregnancy, childbirth, postpartum, neonates, and family planning. The first stage of Mrs. "A"'s labor went normally, with the second stage of delayed cutting of the umbilical cord for 60 minutes. The treatment carried out is to observe the progress and condition of the fetus and it is running well and has no problems. There are still many mothers who give birth with delays in cutting the umbilical cord due to the lack of choice of place of birth with delays in the umbilical cord.